2023
DOI: 10.1126/sciimmunol.abl9041
|View full text |Cite
|
Sign up to set email alerts
|

Dampening type 2 properties of group 2 innate lymphoid cells by a gammaherpesvirus infection reprograms alveolar macrophages

Abstract: Immunological dysregulation in asthma is associated with changes in exposure to microorganisms early in life. Gammaherpesviruses (γHVs), such as Epstein-Barr virus, are widespread human viruses that establish lifelong infection and profoundly shape host immunity. Using murid herpesvirus 4 (MuHV-4), a mouse γHV, we show that after infection, lung-resident and recruited group 2 innate lymphoid cells (ILC2s) exhibit a reduced ability to expand and produce type 2 cytokines in response to house dust mites, thereby … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 93 publications
0
6
0
Order By: Relevance
“…IL-13 is required for the early polarization and maintenance of AMs, but also MO-AMs, in an M2 state in adult mice ( 87 ). Likewise, we have recently highlighted the crucial role that pulmonary ILC2s play in conferring identity and functional polarization to MOs that differentiate into AMs during life ( 88 ). In particular, we have shown that after Murid herpesvirus 4 (MuHV-4) infection, a mouse γHV, lung ILC2s exhibit a reduced ability to produce type 2 cytokines in response to HDM, thereby contributing to protection against allergic airway inflammation.…”
Section: Innate Lymphoid Cells Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-13 is required for the early polarization and maintenance of AMs, but also MO-AMs, in an M2 state in adult mice ( 87 ). Likewise, we have recently highlighted the crucial role that pulmonary ILC2s play in conferring identity and functional polarization to MOs that differentiate into AMs during life ( 88 ). In particular, we have shown that after Murid herpesvirus 4 (MuHV-4) infection, a mouse γHV, lung ILC2s exhibit a reduced ability to produce type 2 cytokines in response to HDM, thereby contributing to protection against allergic airway inflammation.…”
Section: Innate Lymphoid Cells Groupmentioning
confidence: 99%
“…This general skewing towards type 2 inflammation could have a direct effect on asthma susceptibility but could also have an indirect effect on the Th1/Th2 balance later in life by promoting a M2 polarization on AMs and MO-AMs for the long term. In particular, we have recently published a key role for ILC2s in conferring AM identity and polarisation after a virus-induced depletion of the alveolar niche ( 88 ). Deciphering the potential contribution of ‘M2’ AMs (or MO-AMs), trained early in life by activated ILC2s, in long-term sequelae like asthma, could be of major importance in future research.…”
Section: Peripheral or Central Imprinting: How Does Immune Reprogramm...mentioning
confidence: 99%
“…As ILC2 and epithelial cells phenotypes are directly impacted by environmental conditions, the outcome of the experiment largely depends on the environmental conditions to which mice have been subjected, as seen for example with MuHV-4 infection ( Loos et al, 2023 ).…”
Section: General Notes and Troubleshootingmentioning
confidence: 99%
“…Their role in modulating alveolar macrophage (AMs) polarization has been described in early life through the IL-33/ILC2/IL-13 activation cascade, which confers an M2 phenotype to AMs ( Saluzzo et al, 2017 ). In the context of a persistent viral infection, we recently highlighted the essential role of ILC2s as lung niche cells that imprint the tissue-specific identity of monocytes (MOs)-derived AMs and shape their function ( Loos et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation